THE REALITY AND POSSIBILITY OF EMPLOYING THE EUROPEAN EXCELLENCE MODEL (EFQM) IN IRAQI UNIVERSITIES (Case study at Southern Technical University) - Ass. Prof. Dr. Abdulridha Naser Mohsin Al- Malik; Narjis Falih Hassan Al- Saeed (American Journals, 2023)
The research aims to reveal the reality and the possibility of employing the European Model of Excellence (EFQM) in Iraqi universities, specifically in the Southern Technical University, and for the purpose of achieving the goal of the research, the case study approach was employed to reach a set of accurate information and detailed results on the research variables, and then adopt A set of research tools (check list) to measure the level of application of the European Excellence Model (EFQM), and the research community (formations of the Southern Technical University in Basra Governorate) was identified in proportion to the research objectives, in addition to using a set of statistical tools and methods provided by it. The ready-made statistical package program ((SPSS v.26; Excel & SmartPL(.In light of the cognitive and applied research results, the results of the check list showed that the research community (Southern Technical University) has reached an average score of approximately (427 points), which falls according to the ladder of excellence within the second level, which is (organizations known for excellence: 599 – 400 points), in addition to its entry into a number of university rankings, which contributed to its closeness to the European Excellence Model (EFQM).
Keywords: European Organization for Quality Management (EEQM), European Excellence Model.